Synthesis and characterization of barium hexaferrites derived from steel waste by ammonium nitrate salt melt synthesis - Che Muda, Nor Nadhirah; Azis, Raba'ah Syahidah; Hashim, Mansor; Hassan, Jumiah; Sulaiman, Sakinah; Daud, Noruzaman; Mohd Sharani, Nuraine Mariana; Azizan, Abddul Halim; Musa, Makiyyu Abdullahi (Malaysian Solid State Science and Technology Society, 2015)
In this paper, a series of barium hexaferrite BaFe12O19 with different powder to salt ratio (1:3, 1:4, 1:5) were prepared using ammonium salt melt technique. Iron oxide were process from steel waste product were mixed with barium carbonate, used as starting materials to produce barium hexaferrites. The ammonium nitrates in this experiment act as oxidizing agent in this synthesis. The BaFe12O19 powders were sintered at 1300°C for six hours and characterized using X-ray diffraction (XRD), Fourier transform Infrared (FTIR), Vibrating Sample Magnetometer (VSM) and Field emission Scanning Microscope (FeSEM) to investigate its crystallography, magnetic properties and morphology. The maximum coercivity and saturation magnetization obtained for sample ratio 1:3 of 1017 G and 90.9 emu/g, respectively. Increase the salt ratio decrease the coercivity and saturation magnetization values.